2019
DOI: 10.1177/0308518x19869678
|View full text |Cite
|
Sign up to set email alerts
|

Online rental housing market representation and the digital reproduction of urban inequality

Abstract: As the rental housing market moves online, the Internet offers divergent possible futures: either the promise of more-equal access to information for previously marginalized homeseekers, or a reproduction of longstanding information inequalities. Biases in online listings' representativeness could impact different communities' access to housing search information, reinforcing traditional information segregation patterns through a digital divide. They could also circumscribe housing practitioners' and researche… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 67 publications
2
65
1
5
Order By: Relevance
“…Following grow ing rec og ni tion of the value of data col lected online for under stand ing demo graphic pro cesses (Cesare et al 2018), we exam ine adver tise ments col lected from Craigslist. Not all rental hous ing in the United States is adver tised on Craigslist; indeed, Boeing (2020) found that adver tise ments for rental hous ing on Craigslist in Unequal Availability of Rental Housing Information 2014 were over rep re sented in neigh bor hoods with higher shares of White res i dents, dem on strat ing how offline inequalities are reproduced in the sup ply of infor ma tion online. However, our goal is to under stand what kind of infor ma tion is shared on Craigslist, the most com pre hen sive and timely source of hous ing mar ket infor ma tion in the United States (Boeing and Waddell 2017;Kuk et al 2021).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Following grow ing rec og ni tion of the value of data col lected online for under stand ing demo graphic pro cesses (Cesare et al 2018), we exam ine adver tise ments col lected from Craigslist. Not all rental hous ing in the United States is adver tised on Craigslist; indeed, Boeing (2020) found that adver tise ments for rental hous ing on Craigslist in Unequal Availability of Rental Housing Information 2014 were over rep re sented in neigh bor hoods with higher shares of White res i dents, dem on strat ing how offline inequalities are reproduced in the sup ply of infor ma tion online. However, our goal is to under stand what kind of infor ma tion is shared on Craigslist, the most com pre hen sive and timely source of hous ing mar ket infor ma tion in the United States (Boeing and Waddell 2017;Kuk et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…10 We exam ine these var i ables, which mea sure either the qual ity of the units in a neigh bor hood or neigh bor hood demo graph ics, because they could plau si bly affect the ways land lords list their units. For exam ple, a more highly edu cated renter pool could prompt land lords to adver tise cer tain types of ame ni ties, whereas a higher vacancy rate might cre ate more com pe ti tion for poten tial rent ers and prompt land lords to add more infor ma tion to their list ings (Boeing et al 2020).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations